"To Foreign Climes Unknown Before / E'en to Amerique's Distant Shore" The Mission to Establish the First Women's Convent in the Original United States, Told in Carmelite Poetry. - HANNA, DANIEL J. (Early American Studies, An Interdisciplinary Journal)
When Carmelite nuns from Europe crossed the Atlantic in the late eighteenth century to found the first women's convent in the original United States, they brought with them a poetic tradition that can be traced back to the founder of the reformed Carmelite order, Saint Teresa of Avila. In poems that describe their struggles in Europe to escape religious repression, their arduous ocean voyage to America, and finally the foundation of the first convent for religious women in the state of Maryland, the Carmelites who traveled from Europe to the United States both recounted their extraordinary experiences and paid homage to their spiritual mother, Teresa of Avila, who had instigated a tradition of convent poetry in sixteenth-century Spain hundreds of years earlier. These previously unstudied and unpublished poems, presented in this article for the first time, are the earliest known evidence of the spirituality and literary tradition of Teresa of Avila in the United States.